2006
DOI: 10.1902/jop.2006.050293
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Matrix Metalloproteinases (MMP‐8 and ‐9) in Chronic Periodontitis Patients With and Without Diabetes Mellitus

Abstract: An increased concentration of MMP-8 and -9 in the gingival tissue of diabetic CP patients suggests that the expression of these MMPs contributes to the failure of the healing process in the diabetic condition. Treatment strategies directed toward the inhibition of these MMPs could lead to an improved healing rate in CP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
87
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(103 citation statements)
references
References 38 publications
11
87
0
5
Order By: Relevance
“…We found that MMP-8 increases in patients who are diabetic as compared to control which is in accordance with the study of Kumar et al (28) who reported a significant increase in gingival tissue MMP 8 level in diabetic patients having chronic periodontitis as compared to controls. Another study by Gupta et al (29) also reported a rise in salivary MMP-8 levels as compared to nondiabetic controls.…”
Section: Discussionsupporting
confidence: 92%
“…We found that MMP-8 increases in patients who are diabetic as compared to control which is in accordance with the study of Kumar et al (28) who reported a significant increase in gingival tissue MMP 8 level in diabetic patients having chronic periodontitis as compared to controls. Another study by Gupta et al (29) also reported a rise in salivary MMP-8 levels as compared to nondiabetic controls.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, nicotine administration caused a change in fibroblast activity due to the change of collagene fiber synthesis and decreased MMP2 expression. Several MMPs have been identified in the inflamed gingival tissues: MMP-1, -2, -3, -8, -9, -13, produced by the keratinocytes, macrophages, polymorphonuclear leukocytes [2,3,6,26,27]. Their activity could be different depending on the severity of disease and the needs for extracellular matrix digestion.…”
Section: Discussionmentioning
confidence: 99%
“…A study suggested that MMP-9 levels in the gingival crevicular fluid are higher in chronic periodontitis group than in patients with gingivitis and healthy subjects [23]. Similarly another study demonstrated an increased concentration of MMP-9 in the gingival tissue of diabetic chronic periodontitis patients suggests that the expression of these MMPs contributes to the failure of the healing process in the diabetic condition [24]. Prostaglandin E2 and MMP-9 both are well known pro-inflammatory markers for periodontal disease and BTC induces upregulation of both of these markers.…”
Section: Groupmentioning
confidence: 99%